Heavy metal content of some Hungarian and English karst soils - Bárány-Kevei Ilona (Acta climatologica, 2001)
The heavy metal content of karst soils is a significant aspect of karst water because 25% of drinking water comes from the karstwater of the world. The pollution (especially the heavy metal pollution) of the soils is dangerous for karst areas. If the metals pass from the soil into the karst water it will be unhealthy for the population. Much heavy metal is inherited from dry and wet deposition. Acid dry and wet depositions bring pollution materials and give rise to acidification of soils. Soils which have appropriate characteristics can bind the heavy metals to the different soil particles. This power to prevent the heavy metals reaching soil solution mainly depends on the pH, the organic matter and clay content of the soils, namely on the buffering capacity of the soil. The soils with high buffering capacity can accumulate the dangerous metals in the soils and do not permit them to go to soil solution and thus to reach the limestone bedrock and finally the karst water. Generally, the mobility of heavy metals increases with decreasing pH and decreasing organic matter content of soils. Our paper presents the heavy metal content of karst soils in some English and Hungarian karst territories. The analysis of soils attempts to detect the connection between the organic matter content, pH and the heavy metal content of these soils. In the karst-literature we have as yet few data concerning heavy metal contamination of karst soils. Our data indicate the pollution level of karst soils. These data are a basic point for further investigations.